Use of compound specific isotope analysis approach to monitor the aging process of Italian balsamic vinegars - Lisa Lancellotti; Veronica D'Eusanio; Lorenzo Morelli; Eleonora Truzzi; Andrea Marchetti; Lorenzo Tassi (Current Research in Food Science)
Stable isotope analysis has become a valuable tool for studying food chain processes and verifying the authenticity and geographical origin of typical products. The analysis is particularly important for those foods with geographical indications, such as Aceto Balsamico Tradizionale di Modena labelled with the protected designation of origin mark (ABTM PDO) and Aceto Balsamico di Modena with the protected geographical indication (ABM PGI). Understanding how the aging process affects the isotopic composition of specific compounds in ABTM is important for distinguishing between traditional and non-traditional products, as well as for verifying their authenticity. Previous studies have explored isotopic variations in balsamic vinegars, but challenges remain in fully understanding how aging influences isotopic ratios and fractionation phenomena particularly for individual compounds such as glucose, fructose, and acetic acid. This study investigated the impact of aging on the isotopic ratios in Italian balsamic vinegar, focusing on δ18O of water and δ13C of glucose, fructose, and acetic acid. Bulk variables such as water content, density, total acidity, refractive index, and glucose and fructose concentration were also evaluated. The findings revealed that δ18O values of water progressively increased with aging inside the casks’ series for ABTM, allowing a clear differentiation between traditional and non-traditional balsamic vinegars. In contrast, the δ13C values of glucose, fructose, and acetic acid were also influenced by the conditions of production and origins of the starting raw materials. Further research is needed to better understand the effects of the individual factors that influence the δ13C values for enhancing the ability to authenticate and differentiate balsamic vinegar products.